The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1097/mcg.0000000000001923
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic is Associated With Increased Prevalence of GERD and Decreased GERD-related Quality of Life

Ahmad Fauzi,
Daniel M. Simadibrata,
Dewi Friska
et al.

Abstract: Introduction: The prevalence of gastroesophageal reflux disease (GERD) is expected to increase during the pandemic due to unexpected, sudden lifestyle changes such as decreased physical activity and worsening mental conditions. Here, we aim to explore the difference in the prevalence of GERD and GERD-related quality of life (QoL) in Indonesia during the COVID-19 pandemic compared with before the COVID-19 pandemic. Methods: Retrospective analysis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…GI symptoms are known to occur in 29% of patients six months after recovery from COVID-19 infection, and, among these, reflux symptoms were reported in 27% [11]. In an Indonesian survey comprising 9,800 patients, it was found that there was an increased rate of GERD during the pandemic compared to the prepandemic period (67.9% vs. 61.8%, respectively, p<0.001) [12]. Other investigators attribute the worsening GERD symptoms to the restrictive lockdown measures during the pandemic [13].…”
Section: Discussionmentioning
confidence: 99%
“…GI symptoms are known to occur in 29% of patients six months after recovery from COVID-19 infection, and, among these, reflux symptoms were reported in 27% [11]. In an Indonesian survey comprising 9,800 patients, it was found that there was an increased rate of GERD during the pandemic compared to the prepandemic period (67.9% vs. 61.8%, respectively, p<0.001) [12]. Other investigators attribute the worsening GERD symptoms to the restrictive lockdown measures during the pandemic [13].…”
Section: Discussionmentioning
confidence: 99%